Bacterial Peptides and Bacteriocins as a Promising Therapy for Solid Tumor - Yaghoubi, Atieh; Ghazvini, Kiarash; Hasanian, Seyed M.; Avan, Amir; Soleimanpour, Saman; Khazaei, Majid (Current Pharmaceutical Design, 2022)
The conventional treatment is faced with limitations in treating solid tumors due to their specific pathophysiology. Several novel therapeutics have been introduced in recent decades to treat solid tumors. Among these new methods, tumor therapy using bacterial products like bacteriocins and peptides has been of great interest due to their unique characteristics and advantages of them in comparison to the conventional treatment, including that they can precisely target tumor cells, selective toxicity for tumor cells, low side effect on normal cells, toxicity activity for MDR cancer cells, used as the target delivery vehicles and enhancing drug delivery. Moreover, their small size and low molecular weight have made them easy to synthesize and modify. Furthermore, in recent years, genetic engineering has expanded the therapeutic ability of peptides to treat solid tumors, which results in overcoming the peptide drawbacks. The present review mainly focuses on the new advances in applying bacterial peptides and bacteriocins in treating human solid tumors.
Keywords: treatment